Cyclic AMP-response element regulated cell cycle arrests in cancer cells. - Ping Wang; Shuaishuai Huang; Feng Wang; Yu Ren; Michael Hehir; Xue Wang; Jie Cai (PLoS ONE)
Recently, we have demonstrated that trichosanthin (TCS), a promising agent for the treatment of cervical adenocarcinoma, inhibited HeLa cell proliferation through the PKC/MAPK/CREB signal pathway. Furthermore, TCS down-regulated Bcl-2 expression was abrogated by a decoy oligonucleotide (OGN) to the cyclic AMP-responsive element (CRE). The decoy OGN blocked the binding of CRE-binding protein (CREB) to Bcl-2. These results suggested that CRE-mediated gene expression may play a pivotal role in HeLa cell proliferation. However, little is known about the effect of TCS on cell cycle arrests, particularly, whether the genes involved in cell cycle were regulated by CRE. Our present study shows that the arrests of S, G1 and G2/M phases were accompanied by the significant down-regulation of cyclin A, D1 and CDK 2, 4 in HeLa cells, cyclin D1, E and CDK 2, 4 in Caski and C33a cells, and cyclin A, B1, E and CDK 2 in SW1990 cells. However, the cell cycle arrests were reversed via the significant up-regulation of cyclin A and D1, by the combined treatment of TCS and CRE. In conclusion, these data demonstrate for the first time that specific cell cycle arrests in cancer cells can be induced by TCS by inhibiting the binding of CREB to CRE on genes related to cell proliferation.